Información tecnológica
"Dedicated to the transmission of scientific and technological information in Iberoamerica. In its broad coverage, the journal publishes original articles in all areas of applied sciences, technology and engineering, with the condition of being the product of scientific research work and that the work has relevant impact on the development of our Iberoamerican countries."--Journal home page.